"¡Abajo el patriarcado, se va a caer!". The recent regulation on voluntary termination of pregnancy in Argentina and the role of feminist movements (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The contribution aims at analysing the regulation of abortionin Argentina (Ley 27610/2021), tracing the path that led to the approvalof the law. In particular, it will focus on the various steps that, froma jurisprudential and administrative point of view, have accompanied thecountry from the end of the military dictatorship to the present day.The paper will show the fundamental and transversal role that women'sand feminist movements have played in Argentina within this trajectory,providing an opportunity to reflect on the relationship between law,rights and social components.
Keywords: Abortion; Constitutional law and Feminist movements; Argentina; Sexual and reproductive health